2022
DOI: 10.1186/s43141-022-00423-3
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol-lowering effects and safety assessment of Lactobacillus spp. in vivo and in vitro testing for human use as probiotic from the dairy product in Egypt

Abstract: Background The toxicity profile of lactobacilli may be strain dependent, so it should be considered for safe utilization of probiotics. Further, in vivo studies are necessary to evaluate their safety. Result The ability of various probiotic strains to hydrolyze bile salts has been confirmed without noticeable hemolytic activity. Results revealed the presence of α-glucosidase, β-glucosidase, α-galactosidase, and β-galactosidase activity in all inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…The current systematic review and meta-analysis (seven eligible trials with 274 participants) carried out by Pourrajab et al (2020) confirmed that yogurt consumption could reduce cholesterol levels in the blood by up to -8.73 mg/dL. Similarly, Fadl and Kamel. (2022) found that probiotics from Egyptian yogurt, such as L. casei, L. lactis, and L. acidophilus, have the bile salt hydrolysis gene, which is related to cholesterol reduction effects in the blood.…”
Section: Probiotics In Dairy Products and Their Impact On Lowering Bo...supporting
confidence: 64%
See 1 more Smart Citation
“…The current systematic review and meta-analysis (seven eligible trials with 274 participants) carried out by Pourrajab et al (2020) confirmed that yogurt consumption could reduce cholesterol levels in the blood by up to -8.73 mg/dL. Similarly, Fadl and Kamel. (2022) found that probiotics from Egyptian yogurt, such as L. casei, L. lactis, and L. acidophilus, have the bile salt hydrolysis gene, which is related to cholesterol reduction effects in the blood.…”
Section: Probiotics In Dairy Products and Their Impact On Lowering Bo...supporting
confidence: 64%
“…Recently conducted studies have shown that probiotics help to lower cholesterol levels in both human body and dairy products; this is an essential factor for reducing the risk of NCDs (Fadl and Kamel, 2022;Frappier et al, 2022;Ishimwe et al, 2015;Sivamaruthi et al, 2019). The mechanism of probiotics in lowering cholesterol levels (Figure 3) is as follows (Sun and Buys, 2015):…”
Section: How Do Probiotics Lower Cholesterol Levels and Reduce Satura...mentioning
confidence: 99%
“…The mean free vitality of adsorption (E) was stated as 2.62 kJ mol −1 2 , 25 , 26 . According to the overall findings, 98.2% of U (VI) was absorbed through the biosorption of the U models used to compute adsorption capacity: Equations show that the same beads might be utilized for biosorption for 15 days, thus the evaluated value of 2.62 kJ mol −1 This suggests physiosorption as the process but also mentions chemisorption, which involves valence forces through the sharing or exchange of electrons between the sorbent and the sorbate, complexation, coordination, and/or chelation 2 , 3 , 27 . The heat of the adsorption of metal ions suggests that a physical mechanism underlies adsorption.…”
Section: Resultsmentioning
confidence: 99%
“…To make the therapeutic formulation, it is also essential to consider the physiochemical parameters associated with the food products that influence the probiotic viability and functionality during production and preservation [Figure 1]. Intrinsic product parameters such as pH, salt, oxygen concentration, water, sugar content, and other elements such as fermentation settings and microbiological parameters, are among these factors [10]. On an industrial scale, including probiotics in meals poses several microbiological, technological, and economic problems.…”
Section: Probiotic Viability: What Factors Affect It?mentioning
confidence: 99%